Upaya Pencegahan Sikap Bullying Melalui Sosialisasi di SDN 16 Koto Tuo Kec. Barangin Kota Sawahlunto - Anggun Permata Sari; Alfinatul Akbar; Muhammad A’ras Sadiq; Pebrika Zuliani; Salmaa Zainabila; Laura Dwi Fortuna; Hafizul Fikri Aritonang; Muhammad Arief Syaputra (Lembaga Pengembangan Kinerja Dosen, 2025)
Character education in elementary schools is important to prevent bullying behavior among students. This article discusses efforts to prevent bullying attitudes through socialization at SDN 16 Koto Tuо, Kec. Barangin, Sawah Lunto City. The research method used was to deliver the material directly and a question and answer session, attended by 35 students. The results of the socialization showed an increase in students' awareness and motivation not to bully, although there were minor obstacles in the form of a less conducive atmosphere during the socialization. Student participation in this activity was very high, reflecting their enthusiasm for the material presented. This socialization not only aims to provide an understanding of the negative impacts of bullying, but also to build empathy and mutual respect among students. By actively involving students, it is hoped that they can better understand the importance of creating a safe and comfortable environment for all classmates. This effort is expected to be a model for other schools in overcoming the problem of bullying and increasing awareness of the importance of respectful behavior among children. Thus, this socialization is expected to contribute to creating a safer school environment and supporting the development of positive student character, as well as reducing the incidence of bullying in the future.